Evaluation of diesel engine performance and emissions fueled with waste cooking oil biodiesel-plastic pyrolysis oil blends. - Amanu Aulia; Ilmi Abdullah; Abdi Hanra Sebayang (Politeknik Negeri Lhokseumawe, 2026)
The depletion of petroleum reserves, rising fossil fuel demand, and increasing plastic waste pollution highlight the need for alternative fuels. This study investigated the performance and exhaust emissions of a direct-injection diesel engine fueled with waste cooking oil biodiesel blended with plastic pyrolysis oil at concentrations of 5%, 10%, 15%, and 20% (B+A5 to B+A20). Biodiesel was produced through degumming, esterification, and transesterification, while plastic pyrolysis oil was obtained via thermal cracking. Engine tests under a constant load across a range of engine speeds evaluated brake power, brake-specific fuel consumption (BSFC), brake thermal efficiency (BTE), and exhaust emissions. The results indicate that increasing the proportion of plastic pyrolysis oil improved engine performance compared to pure biodiesel. The B+A20 blend provided the best overall performance, with 44.4% higher power output, 39.6% higher BTE, and 30% lower BSFC than biodiesel, although performance remained below conventional diesel. Regarding emissions, B+A20 reduced CO by 16.3% relative to biodiesel and slightly reduced CO₂ (1%), while NOx increased by 59.7%, highlighting a trade-off between improved performance and NOx control. Overall, blending waste cooking oil biodiesel with plastic pyrolysis oil enhances renewable fuel performance and valorizes plastic waste, but further measures are needed to mitigate NOx emissions.